The Modern Halaqah: Recontextualizing Bahtsul Masail Tradition as a Pedagogical Strategy for Critical Inquiry and Academic Excellence in Islamic Education Management - Abdul Halim; Faiz Faricha (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2025)
The stagnation of academic culture in Islamic Higher Education (PTKI) demands a transformative intervention to shift the paradigm from passive learning to critical inquiry. This study analyzes the revitalization of academic culture through "Majelis Dialektika" (Dialectical Assembly) and its implications for reconstructing critical reasoning and student achievement at the Islamic Education Management (MPI) Program, IAI Al Muhammad Cepu. Employing a qualitative case study design, data were gathered through participant observation, documentation, and in-depth interviews with key informants, including the Head of Study Program, facilitators, and high-achieving students. The findings reveal that: (1) Majelis Dialektika has transformed from a peripheral activity into a core mechanism for academic interaction; (2) It successfully reconstructs students' cognitive structures from textual taqlid to "Managerial Ijtihad"  an integrative critical logic combining modern management theory with Ushul Fiqh; and (3) Participation intensity correlates positively with enhanced academic self-efficacy and scholarly achievement. This study concludes that integrating Islamic debate traditions into management education is vital for producing adaptive education leaders.